Peranan Pola Asuh Orang Tua dalam Pembentukan Karakter Anak - Solihin Slamet Kusdi (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2018)
This article addresses the topic of family, which reviews that the family has an important role in shaping the child character. The used approach is a naturalistic approach which is often called a qualitative approach. To obtain valid data used data collection techniques that include interviews, observation and documentation. Furthermore, data analysis is carried out involving data organization. This discussion found that as a smallest system, families instill moral values of a child's personality. During the growth period a child has many questions about things that are felt new. Children have critical questions, this is where good communication skills are required by parents in answering questions raised by children. Families now have more complex functions that include the functions of production and consumption. This writing needs to be done so that readers can have a view on how the family influences the development of a child's character. In the end it can be said that the family has an important role in shaping the child character.